Mothers Awareness of Pneumonia and the Toddler Breastfeeding Duration Affect Pneumonia Incidence - Primal, Def; Jafri, Yendrizal; Fernandes, Andrye (JOSING: Journal of Nursing and Health, 2021)
This study aims to determine the relationship between the mother's level of awareness about the pathology of pneumonia and the duration of breastfeeding under five with the incidence of pneumonia in DR. M.A. Hospital Hanafiah. This research is a retrospective analytic descriptive study with a cross-sectional design. The results showed that mothers' awareness of pneumonia was lower by 71.8%, they breastfed their babies for less than six months (71.8%), and more than two-thirds of children under five (76.9%) were diagnosed with pneumonia. Furthermore, statistical analysis significantly correlated the mothers' awareness of pneumonia and the duration of breastfeeding they performed on their children with pneumonia. The conclusion is that the mother's understanding of pneumonia has a linear effect on the incidence of pneumonia in infants and toddlers. The duration of breastfeeding has a significant impact. We assume that non-exclusive breastfeeding in infants stimulates underweight and immunological disorders that accelerate the incidence of pneumonia. Keywords: Mother's Awareness, Length of Breastfeeding, Toddler Pneumonia